Before the Ink Is Dry: Does Sustainability Reduce Earnings Management? Theoretical Perspective - Alwadhan, Ahmad; Abed, Suzan (International Journal of Accounting and Financial Reporting, 2021)
This paper reviews the field of sustainability to develop insights into earnings management studies and outline future research opportunities. We find that most previous studies use integrated reports measured by three dimensions of social, economic and environmental sustainability. These three dimensions are interrelated and communicate with each other to formulate the definition of sustainability. And the sustainability report should provide a balanced disclosure of sustainability performance, including both positive and negative contribution. This paper offers an insightful analysis into sustainability disclosure to support the analysis of IR benefits to balance the current literature that overlooks the benefits of IR.